Inosine triphosphatase allele frequency and association with ribavirin-induced anaemia in Brazilian patients receiving antiviral therapy for chronic hepatitis C - Nathália Delvaux; Vanessa Duarte da Costa; Maristella Matos da Costa; Livia Melo Villar; Henrique Sérgio Moraes Coelho; Eliane Bordalo Cathalá Esberard; Priscila Pollo Flores; Carlos Eduardo Brandão-Mello; Cristiane Alves Villela-Nogueira; Adilson José de Almeida; Elisabeth Lampe (Memorias do Instituto Oswaldo Cruz, 2015)
Inosine triphosphatase (ITPA) single nucleotide polymorphisms (SNPs) are strongly associated with protection against ribavirin (RBV)-induced anaemia in European, American and Asian patients; however, there is a paucity of data for Brazilian patients. The aim of this study was to evaluate the ITPA SNP (rs7270101/rs1127354) frequency in healthy and hepatitis C virus (HCV)-infected patients from Brazil and the association with the development of severe anaemia during antiviral therapy. ITPA SNPs were determined in 200 HCV infected patients and 100 healthy individuals by sequencing. Biochemical parameters and haemoglobin (Hb) levels were analysed in 97 patients who underwent antiviral therapy. A combination of AArs7270101+CCrs1127354 (100% ITPase activity) was observed in 236/300 individuals. Anaemia was observed in 87.5% and 86.2% of treated patients with AA (rs7270101) and CC genotypes (rs1127354), respectively. Men with AA (rs7270101) showed a considerable reduction in Hb at week 12 compared to those with AC/CC (p = 0.1475). In women, there was no influence of genotype (p = 0.5295). For rs1127354, men with the CC genotype also showed a sudden reduction in Hb compared to those with AC. Allelic distribution of rs7270101 and rs1127354 shows high rates of the genotypes AA and CC, respectively, suggesting that the study population had a great propensity for developing RBV-induced anaemia. A progressive Hb reduction during treatment was observed; however, this reduction was greater in men at week 12 than in women.